2008
DOI: 10.1308/003588408x318219
|View full text |Cite
|
Sign up to set email alerts
|

www.Accurate Information for Varicose Vein patients.com?

Abstract: INTRODUCTION The aim of this study was to review the information available to the public regarding the treatment of varicose veins on dedicated UK-based websites. PATIENTS AND METHODS Websites were identified by using the Google® search engine. All identified websites were examined, noting the range of treatments explained and their stated potential complications. Website ownership was also recorded. RESULTS A total of 49 websites were identified, belonging to individual physicians (21), private clinics or gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The authors also indicated that these web sites did not include any information on the complications that may possibly be encountered following these treatments. 12 This finding is consistent with our results, suggesting there is generally insufficient information on treatment outcomes in internet media. The content of YouTube videos is determined by the preferences of the uploader; there is no restriction or selection in the process.…”
Section: Discussionsupporting
confidence: 92%
“…The authors also indicated that these web sites did not include any information on the complications that may possibly be encountered following these treatments. 12 This finding is consistent with our results, suggesting there is generally insufficient information on treatment outcomes in internet media. The content of YouTube videos is determined by the preferences of the uploader; there is no restriction or selection in the process.…”
Section: Discussionsupporting
confidence: 92%
“…13 A recent investigation of the information available to patients with varicose veins on the Internet found that less than 50% of websites discussed all treatment options and many failed to warn of potential complications. 18 Ideally, patients should be provided with information about all potential treatment options, including the advantages and disadvantages, even if they are not available at that particular hospital, and should be allowed to express a preference as to where they are treated.…”
Section: Discussionmentioning
confidence: 99%
“…5 It has also been shown that a number of Web sites fail to give accurate information about complications following endovenous treatments. 6 The published results of randomized clinical trials comparing surgery to endovenous thermal ablation have frequently shown endovenous procedures to offer reduced postoperative pain, less bruising, and faster return to normal activity. However, outcomes following the 2 modalities are comparable with respect to obliteration of superficial reflux, 7,8 safety, 7 complications, 9 alleviation of symptoms, 7,8 speed of procedure, 9 recurrence, 10,11 and cost.…”
Section: Introductionmentioning
confidence: 99%